Properties of Thermoplastic Elastomers Made of MAH-g-EPDM, Zinc Oxide and Amino Acids - Kwon1, Hyuk-Min; Kim1, Yeowool; Choi1, Sung-Seen; Woo Bae2, Jong; Kim2, Jung-Soo (Asian Journal of Chemistry, 2013)
Thermoplastic elastomers were prepared by mixing maleic anhydride-grafted ethylene-propylene-diene terpolymer (MAH-g-EPDM), zinc oxide and amino acids. 4-Amino-2-methoxybenzoic acid (MBA), 4-aminosalicylic acid, 12-aminolauric acid and L-glutamine were employed as the amino acids. The thermoplastic elastomers were analyzed by infrared spectroscopy (IR), solvent extraction, crosslink density and physical properties. The amino acids reacted with maleic acid groups of the MAH-g-EPDM and zinc oxide to form ionomers. Like cured elastomers, it is possible that crosslink densities of the thermoplastic elastomers are measured using the solvent swelling method. Compared to the specimen without amino acids, crosslink densities of the thermoplastic elastomers decreased due to the long crosslinkages. Crosslink density of the sample containing 12-aminolauric acid was lower than the others. Physical properties of the sample containing 4-aminosalicylic acid were better than the others. This can be explained by the hetero-crosslinkages.